The effects of the heating rate on the pyrolysis behavior of empty fruit bunch biomass - Ahmad Khairul Anwar, Samsuddin (2008)
Pyrolysis is a process to have fuel from biomass. Performance of this process was influenced by some variables which are heating rate, operating temperature, species of biomass, time and particle size. These parameters will affect the product conversion or performance in terms of its percentage of volatiles compound from the sample. This study focus on the effects of heating rate on the pyrolysis behaviour of empty fruit bunch (EFB) biomass. In order to achieve the objective, the TGA is used and EFB is choosing as a sample of biomass. The temperature of pyrolysis experiments were performed at a room temperature till 950°C. The experiment was conducted at the heating rates of 5, 10, 20, 30, 40 and 60 °C /min. Results from experiment conducted showed that at the lower values of this interval of heating rate, the maximum rates of mass losses were so low that they were only 5.6%/min for 5°C/min, and 8.0%/min for 10°C /min. As the heating rate increased, rates of maximum mass losses also increased so that they were determined as 15.6, 25.7 and 35.2%/min for the heating rates of 20, 40 and 60 °C/min, respectively. Total mass losses from the sample were determined as 87.1, 62.8, 61.7, 59.1, and 51.7% at heating rates of 5, 10, 20, 30, 40 and 60 °C /min. The results of this solution pointed out that activation energies were 6.05, 6.83, 8.54, 11.98 and 10.61 kJ/mol for the heating rates of 5, 10, 20, 40 and 60°C/min. This research showed that important differences on the pyrolytic behavior when heating rate is changed. The increasing of heating rates will lead to higher conversion rates. At lower heating rates, the residence time is longer and results in high percentage of mass losses. Activation energy values were first increased when the heating rates increased but further increases of heating rates rapidly declined the activation energy -Author